2020
DOI: 10.1186/s13045-020-00924-z
|View full text |Cite
|
Sign up to set email alerts
|

Proteolysis targeting chimeras (PROTACs) are emerging therapeutics for hematologic malignancies

Abstract: Proteolysis targeting chimeras (PROTACs) are heterobifunctional small molecules that utilize the ubiquitin proteasome system (UPS) to degrade proteins of interest (POI). PROTACs are potentially superior to conventional small molecule inhibitors (SMIs) because of their unique mechanism of action (MOA, i.e., degrading POI in a substoichiometric manner), ability to target "undruggable" and mutant proteins, and improved target selectivity. Therefore, PROTACs have become an emerging technology for the development o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
81
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(81 citation statements)
references
References 251 publications
(358 reference statements)
0
81
0
Order By: Relevance
“…Thus, future efforts aimed at inhibiting the METTL3-eIF3h association may lead to the development of new cancer therapies. Notably, Proteolysis targeting chimeras (PROTACs), which are heterobifunctional small molecules that degrade proteins of interest through ubiquitin proteasome system, are another promising technology for the development of m6A methyltransferase-targeting therapeutics [ 161 ]. In addition, although this review focuses mostly on m6A methyltransferases, studies of m6A erasers have identified several potent inhibitors targeting the demethylase FTO in acute myeloid leukemia [ 162 , 163 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, future efforts aimed at inhibiting the METTL3-eIF3h association may lead to the development of new cancer therapies. Notably, Proteolysis targeting chimeras (PROTACs), which are heterobifunctional small molecules that degrade proteins of interest through ubiquitin proteasome system, are another promising technology for the development of m6A methyltransferase-targeting therapeutics [ 161 ]. In addition, although this review focuses mostly on m6A methyltransferases, studies of m6A erasers have identified several potent inhibitors targeting the demethylase FTO in acute myeloid leukemia [ 162 , 163 ].…”
Section: Discussionmentioning
confidence: 99%
“…The abovementioned approaches including inhibition of protein–protein interactions are partially successful preclinically but less often clinically ( Table 4 ). One of the most promising approaches that recently emerged for hematologic malignancies is PROTACs (proteolysis-targeting chimeras) [ 237 ]. PROTACs are artificial heterobifunctional small molecules that utilize the ubiquitin proteasome system to degrade the proteins of interest.…”
Section: Fusion Proteins As Transcriptional Modulatorsmentioning
confidence: 99%
“…Because of their ability to target mutant or undruggable proteins including fusion proteins, PROTACs can be therapeutically advantageous compared to enzymatic inhibitors. The efficacy of this technology has been reported for inhibition of numerous oncoproteins in a variety of tumors including blood malignancies (reviewed in [ 237 ]). The safety, selectivity, and therapeutic efficacy of PROTACs in hematologic malignancies emerge as hot problems.…”
Section: Fusion Proteins As Transcriptional Modulatorsmentioning
confidence: 99%
“…Although no PTM protein isoform‐specific PROTAC has been reported, a number of PROTACs targeting PTM modification enzymes with potent selectivity, including CDK and BCR‐ABL kinases, and histone methylation enzyme complex PRC2, have been reported 366 . For example, selectively targeting cyclin‐dependent kinase 6 (CDK6) with ATP‐competitive small molecules has been challenging by virtue of the presence of an identical ATP‐binding site in its close homology cyclin‐dependent kinase 4 (CDK4).…”
Section: Potential Directions Of Targeting Ptm Isoforms In Drug Discomentioning
confidence: 99%